Dampak Kemajuan Teknologi Digital Terhadap Pendidikan dan Karakter Moral Peserta Didik di Era Transformasi Digital - Farkhan Maulana; Areta Nasywa; Rissa Ramadhani; Berlian Adinda P.P.; Milda Ayu Akmila; Khusna Ziadatun R.; Muhammad Ariyanto P; Arif Widagdo (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Digital transformation has reshaped educational systems and influenced the moral development of students within contemporary learning environments. This study aimed to critically examine the implications of technological advancement for educational practices and the moral character of students in the digital era. The research employed a systematic literature review with a qualitative descriptive approach through the analysis of academic journals, policy documents, and conceptual studies related to digital literacy, moral education, and educational transformation. The findings indicate that digital technology improves educational accessibility, learning flexibility, and pedagogical innovation while simultaneously intensifying moral challenges including cyberbullying, digital plagiarism, declining critical thinking, post truth orientation, and social individualism. The study also reveals the emergence of cultural lag caused by the imbalance between technological acceleration and moral preparedness within educational institutions. A humanistic digital education model integrating ethical literacy, character education, empathy, and responsible technology governance is required to strengthen moral resilience among students in the twenty first century.